TRANSFORMING HERITAGE BUILDING FOR COMMERCIALISATION - Rani, Prihatmanti; Putri, Cantika; Devina, Adeline (PLANNING MALAYSIA, 2017)
Adaptive reuse is known as one of the conservation methods to prevent the building from being abandoned, dilapidated, as well as to halt further deterioration of the fabrics, both in interior and exterior. Surabaya has a number of Dutch colonial buildings as evidence of the Dutch settlements for 350 years. The aesthetic value, location and the historical significance of the buildings have made the proprietors conserving those buildings and reusing them as commercial spaces. In this research, two prominent Dutch-colonial mansions have been chosen as the research objects. Those buildings have been transformed into an upscale dining place in Surabaya, Indonesia. Based on the local regulation for heritage building conservation, the designated buildings have adhered to the conservation regulations. However, in some parts, alterations were still discovered and not according to the original of the building. These changes were purposely done in order to accommodate the business owners’ need. Therefore, this paper aims to review the transformation of heritage building and the compliance to the regulation.